Relationship Between Inservice Training With Students’ Achievements At TVET Insitutions In Malaysia - Wan Ahmad, Wan Mohd Rashid; Esa, Ahmad; Mohd. Salleh, Berhannudin; Abd Kadir, Zulida; Razali, Hairani (Journal of Technical Education and Training, 2009)
In-service training in the field of Technical Vocational Education and Training (TVET) acts as a catalyst for students’ achievements. Nevertheless, studies on the matter is still lacking especially in the context of its contributions by the teachers attending the training with students’ achievements. This study, thus, aims to identify the effectiveness of in-service training attended by teachers at TVET institutions in Malaysia. Data gathered was collected using two sets of questionnaire, Set A and Set B. Set A was distributed to 43 teachers from technical schools while Set B was given out to 1225 students of the 43 sample teachers. Data collected was recorded and descriptive statistic analysis was carried out using SPSS version 12. Among the analysis carried out was the t-test to identify for differences in students’ achievements whom the teachers taught either by those who have or have not attended any related in-service training. Findings of the study found significant relationship between in-service training attended by the teachers and teachers’ teaching effectiveness, teachers teaching effectiveness with students’ achievements as well as between in-service training with students’ achievements.